Food disgust sensitivity influences the perception of food hazards: Results from longitudinal and cross-cultural studies. (1st October 2020) - Siegrist, Michael; Bearth, Angela; Hartmann, Christina
Abstract: Two survey studies, one conducted in Switzerland and the other in nine countries, suggest that food disgust sensitivity is a personality variable that influences the perception of food hazards. For a large Swiss sample ( N  = 2813), we found that participants having higher food disgust sensitivity perceived more risks compared with participants having lower disgust sensitivity. A longitudinal analysis further suggests that changes in the participants' disgust sensitivity result in changes in the perception of food hazards. A second survey was conducted in Australia, China, England, France, Mexico, South Africa, Spain, Sweden, and the US ( N  = 5511). In all countries except China, significant correlations between food disgust sensitivity and risk perception were observed. The results suggest that food disgust sensitivity may be an important factor for the acceptance of novel or existing agri-food technologies.